2001
DOI: 10.1111/j.1365-2842.2001.tb01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular dysfunction in Turkish children with mixed and permanent dentition

Abstract: This study was carried out to determine the prevalence of temporomandibular joint (TMJ) dysfunction in mixed and permanent dentition and to evaluate the sex distribution in Turkish children. One hundred and eighty-two children with mixed dentition and 212 with permanent dentition were selected for the study, which used a questionnaire and clinical examination. Children with one or more signs (TMJ sounds, TMJ tenderness, muscle tenderness, restricted mouth opening) and/or symptoms (TMJ pain during mastication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 19 publications
(36 reference statements)
2
22
1
10
Order By: Relevance
“…Some earlier studies found such a correlation [40,41], while a more recent study did not [8]. Epidemiological studies have reported signs and symptoms in children to be as frequent as in adults [41,42] and that the reduced prevalence in children could be partly related to the fact that most signs and symptoms in young children are characterized as mild and therefore hard to detect [43].…”
Section: Discussionmentioning
confidence: 96%
“…Some earlier studies found such a correlation [40,41], while a more recent study did not [8]. Epidemiological studies have reported signs and symptoms in children to be as frequent as in adults [41,42] and that the reduced prevalence in children could be partly related to the fact that most signs and symptoms in young children are characterized as mild and therefore hard to detect [43].…”
Section: Discussionmentioning
confidence: 96%
“…The questionnaire used in this study was adapted from similar questionnaires used to examine TMD in children and adolescents and was implemented through interviews. Before conducting the survey, the questionnaire was administered to 40 children who were not included in the study and their responses were evaluated for clarity and comprehensibility.…”
Section: Methodsmentioning
confidence: 99%
“…While TMD generally affects adults, epidemiological studies have reported signs and symptoms of TMD in #bib11 #bib12 #bib13 #bib14 #bib15 % of children and adolescents. Given these prevalence rates, additional research is needed to evaluate TMD in younger individuals, since early diagnosis may prevent the disease from progressing to a stage where it causes irreversible destruction of the intra‐capsular structures of the TMJ and affect normal craniofacial growth.…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent clinical signs of TMD are TMJ sounds (upon palpation), limitation of mandibular movements, TMJ and muscle tenderness [2,3]. Symptoms, such as headache, TMJ sounds, bruxism, difficulty in opening the mouth, jaw pain and facial pain have been reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…TMD have generally been presumed to be conditions affecting only adults; however, epidemiological studies have reported signs and symptoms in children and adolescents to be as frequent as in adults [2]. The most prevalent clinical signs of TMD are TMJ sounds (upon palpation), limitation of mandibular movements, TMJ and muscle tenderness [2,3].…”
Section: Introductionmentioning
confidence: 99%